D-band center optimization of iron carbide via Cr substitution for enhanced alkaline hydrogen evolution. (October 2022) - Zhang, Yu; Zhang, Yuefeng; Tian, Bin; Li, Hao; Zeng, Zhiyuan; Ho, Derek
Abstract: Iron carbide (Fe3 C) with metallic properties is a good candidate for water oxidation. However, it exhibits poor performance toward hydrogen evolution reaction (HER) due to weak hydrogen desorption induced by an unfavorable d-band center energy level of the Fe site. In this work, we present a new technique for enhancing alkaline hydrogen evolution through tuning the d-band center energy level. A Cr-doped Fe3 C@carbon core–shell structure grown on a N-doped graphitic framework (Cr–Fe3 C@C-NGF) is presented, demonstrating high HER activity. Cr–Fe3 C@C-NGF with the optimal Cr doping level of 0.81 wt% exhibits an overpotential of 126 mV at 10 mA cm −2, which is substantially lower than that of the pristine Fe3 C@C-NGF (257 mV). Experimental results and density functional theory calculations both suggest that Cr doping downshifts the d-band center energy level, which accelerates hydrogen desorption from the Fe sites, thus improving HER performance. This work may open a key avenue for the optimization of Fe3 C-based HER electrocatalysts via modulation of the d-band energy level. Graphical abstract: Image 1 Highlights: A novel d-band center modulation strategy via Cr doping is proposed. Cr doping induces a downshift of d-band center, which promotes H2 desorption from Fe sites. A dramatically enhanced activity over Fe sites towards hydrogen evolution can be observed after Cr doping.